2022
DOI: 10.1149/1945-7111/ac6459
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Rich O2-Type Li0.66[Li0.22Ru0.78]O2 Positive Electrode Material

Abstract: Increasing the energy density of lithium-ion batteries is an important step towards flexible electricity supply, which can be achieved by developing large-capacity positive electrodes. Lithium-rich oxides have been a longstanding research target because of their large capacity involving extra oxygen-redox reactions. In this work, we report the synthesis, electrochemical properties, electronic structure, and structural evolution of O2-type lithium-rich layered oxide Li1.22‒x Ru0.78O2. A robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…36,37 Both electrodes could deliver a high discharge capacity of 239 and 244 mA h g −1 , respectively, with a remarkably small first-cycle irreversible capacities, which is hard to achieve with conventional O3-type lithium-rich layered oxide electrodes, indicating the superior electrochemical stability of O2-type oxygen redox electrodes. 14,23,24,26–28 While LLNMO and LLCMO electrodes exhibited similar initial electrochemical properties to each other, a noticeable difference was observed in the voltage retention behavior over extended cycling experiments. Fig.…”
Section: Structural and Electrochemical Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…36,37 Both electrodes could deliver a high discharge capacity of 239 and 244 mA h g −1 , respectively, with a remarkably small first-cycle irreversible capacities, which is hard to achieve with conventional O3-type lithium-rich layered oxide electrodes, indicating the superior electrochemical stability of O2-type oxygen redox electrodes. 14,23,24,26–28 While LLNMO and LLCMO electrodes exhibited similar initial electrochemical properties to each other, a noticeable difference was observed in the voltage retention behavior over extended cycling experiments. Fig.…”
Section: Structural and Electrochemical Propertiesmentioning
confidence: 96%
“…It shows that the average discharge voltages were relatively well maintained for both LLNMO and LLCMO electrodes, which is in contrast to the O3-type counterparts that exhibited rapid voltage decay within a few cycles, consistent with previous literature reports. 14,23,24,26–28 Nevertheless, a slightly greater degree of the voltage decay was evidenced for the LLCMO electrode (93.8% retention) compared with the LLNMO (98.4%), even though they commonly shared the O2-type structure that is effective in suppressing the voltage decay. 14,23–29 Considering that the voltage decay is primarily coupled with the irreversible transition metal migration, 13–17 it may be inferred that the LLCMO electrode has undergone the structural transition involving the irreversible transition metal migration during cycles, which will be verified in detail later.…”
Section: Structural and Electrochemical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…13 where the Ru migration is successfully blocked owing to the nature of the O2 stacking. 17 O2-type Li-rich layered oxides are metastable and cannot be obtained by common high-temperature solid-state lithiation methods (>600 °C). Their synthesis requires much lower temperatures of 120−300 °C that can only be achieved by soft chemistry routes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The migration of TM cations would inevitably occur, but the strong electrostatic repulsions would restrict the movement of TM ions in the lithium interslab space and enhance their reversible return within their own original layers . Paulsen et al reported that the layered-to-spinel structural transition did no longer occur in O2-type Li 2/3 [Li 1/6 Mn 5/6 ]­O 2 ; more recently, Umeno et al studied the O2-type Li-rich layered ruthenium oxide Li 1.22– x Ru 0.78 O 2 where the Ru migration is successfully blocked owing to the nature of the O2 stacking …”
Section: Introductionmentioning
confidence: 99%